Infrared and Raman Spectroscopy in Forensic Science - Chalmers, John M; Edwards, Howell G M; Hargreaves, Michael D (West Sessex : John wiley, 2012)
This book will provide a survey of the major areas in which information derived from vibrational spectroscopy investigations and studies have contributed to the benefit of forensic science, either in a complementary or a unique way. This is highlighted by examples taken from real case studies and analyses of forensic relevance, which provide a focus for current and future applications and developments.
Included bibliographical references; Index 603-618p.
Keywords: Criminal investigation; Infrared spectroscopy; Raman spectroscopy; Forensices science